The Role of Consumer Identity and Religious Beliefs in Shaping Repurchase Intention in Halal Food - Rahmawaty, Penny; Haryono, Tulus; Wahyudi, Lilik; Setiawan, Ahmad Ikhwan (Pandawan, 2026)
This study aims to investigate the effect of halal awareness and self-identity on halal food repurchase intention in Indonesia, with product assurance belief acting as a mediating variable and religiosity and community attachment serving as moderating variables. Understanding these relationships is important to explain Muslim consumer behavior in selecting halal food products. The research adopts a quantitative survey approach targeting Muslim consumers in Indonesia. Data were collected using a purposive sampling technique to ensure that respondents met the research criteria. A total of 535 respondents participated in this study. The collected data were analyzed using Structural Equation Modelling-Partial Least Square (SEM-PLS), which allows the simultaneous testing of relationships among multiple variables in the research model. The results of the analysis reveal that halal awareness and self-identity have a significant direct influence on repurchase intention and also affect it indirectly through product assurance belief. This finding indicates that consumers who possess stronger awareness of halal principles and a stronger Muslim self-identity tend to show a higher intention to repurchase halal food products. In addition, product assurance belief significantly influences consumers’ intention to repurchase halal food, highlighting the importance of trust in halal product guarantees. The belief in product assurance is found to partially mediate the relationship between halal awareness, self-identity, and halal food repurchase intention. Furthermore, the results indicate that religiosity does not moderate the relationship between product assurance belief and repurchase intention. Community attachment also does not moderate the influence of halal awareness on repurchase intention. However, it strengthens the relationship between self-identity and product assurance belief toward halal food repurchase intention in Indonesia.